2011
DOI: 10.1155/2011/218483
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation in the C-Terminal Nuclear Localization and Retention Signal (C-NLS) of the EWS Protein

Abstract: Ewing sarcoma (EWS) proto-oncoprotein, an RNA-binding protein, is involved in DNA recombination and repair, gene expression, RNA processing and transport, as well as cell signalling. Chimeric EWS oncoproteins generated by chromosomal translocations between EWSR1 and the genes of transcription factors cause malignant tumors. To understand the loss of function by these translocations, the role of the intact EWS protein has to be investigated. The predominantly nuclear localization of the EWS protein via a transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Once in the cytosol, FET proteins are released from their bound mRNAs by one of the following: mRNP remodeling components, posttranslational modifications that decrease RNA binding, displacement by elongating ribosomes, or ultimately degradation of the bound mRNA. Cytoplasmic FET proteins are then reimported into the nucleus upon transportin recognition of a nontraditional nuclear localization signal (PY-NLS) found at the C terminus of FET proteins (118)(119)(120). Modifications near this PY-NLS sequence, including arginine methylation and tyrosine phosphorylation, alter the cytoplasmic accumulation of the FET proteins (96-98, 118, 120-123).…”
Section: Nuclear-cytoplasmic Shuttling Of Fet Proteinsmentioning
confidence: 99%
“…Once in the cytosol, FET proteins are released from their bound mRNAs by one of the following: mRNP remodeling components, posttranslational modifications that decrease RNA binding, displacement by elongating ribosomes, or ultimately degradation of the bound mRNA. Cytoplasmic FET proteins are then reimported into the nucleus upon transportin recognition of a nontraditional nuclear localization signal (PY-NLS) found at the C terminus of FET proteins (118)(119)(120). Modifications near this PY-NLS sequence, including arginine methylation and tyrosine phosphorylation, alter the cytoplasmic accumulation of the FET proteins (96-98, 118, 120-123).…”
Section: Nuclear-cytoplasmic Shuttling Of Fet Proteinsmentioning
confidence: 99%
“…EWSR1 is an RNA-binding protein that shuttles between the nucleus and cytoplasm, but is predominantly nuclear (29)(30)(31). Given that HCV replicates in the cytoplasm, we next examined the localization of EWSR1 in HCV-infected cells.…”
Section: Ewsr1 Binds Hcv Rna Elementsmentioning
confidence: 99%
“…We identified a novel interaction between the cellular RNA-binding protein EWSR1 and the HCV CRE. EWSR1 is a predominantly nuclear protein that shuttles between the nucleus and cytoplasm (29)(30)(31) and has been previously identified as a potential HCV cofactor in a genome-wide siRNA screen (32). It is a member of the TET family, which regu-lates transcription and RNA processing (33,34).…”
mentioning
confidence: 99%
“…It has been previously reported that FUS undergoes arginine methylation in arginine-glycine-glycine (RGG) domains near to the NLS that impairs TNPO1 binding to RGG domains, inhibiting nuclear import (Rappsilber et al, 2003;Hung et al, 2009;Dormann et al, 2012;Tradewell et al, 2012;Yamaguchi and Kitajo, 2012;Scaramuzzino et al, 2013). Finally, phosphorylation of the C-terminal Y656 residue within the NLS of the EWSR1 protein has been shown to inhibit nuclear import (Leemann-Zakaryan et al, 2011). As FUS and EWSR1 have highly homologous NLS domains, we sought to explore the functional effects of post-translational modifications of the NLS of FUS.…”
Section: Introductionmentioning
confidence: 99%